The length-weight relationship and condition factor of two fish species Planiliza abu and Silurus triostegus from the Tigris River before the construction of the Ilisu and Cizre dams on the river - Bilici, Serbest (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2021)
The research was carried out to determine the length-weight relationships (LWR), and condition factor of two fish species Planiliza abu and Silurus triostegus from the Tigris River where Ilisu and Cizre dams reservoir will occur. LWRs were obtained for three body lengths total, fork and standard for P. abu and total and standard for S. triostegus, by formula of W = aLb. The "b" values ranged from 2.8315 to 3.1293 for P. abu and 2.9066 to 3.0363 for S. triostegus. The relationships were found to be highly significant with all "r2" values being > 0.8572. The Fulton's condition factors (K) and relative condition factor (Kn) were calculated as 1.1534 and 1.0043 for P. abu and as 1.0357 and 1.0294 for S. triostegus respectively.
Keywords: Condition factor; Freshwater fish; Length-weight relationship; Tigris River